Pacific affairs
Pacific Affairs is a peer-reviewed, independent, and interdisciplinary scholarly journal focusing on important current political, economic and social issues throughout Asia and the Pacific. Each issue contains approximately five new articles and 40-50 book reviews. Published continuously as a quarterly since 1928 under the same name, it is the oldest English-language journal with a focus on Asia and the Pacific. It enjoys an international reputation based on the high quality of articles, and its extensive book reviews section.